Quran, Science and Scientific Knowledge Quest Embryology through the Lens of the Holy Quran - GASMI , Aouatef; TELIDJA,Houfa; HACHANI , Siham (Faculty of Letters and Foreign Languages Department of English, 2019)
Ever since the down of mankind, we have sought to understand nature and our existence. For many people, science is the only legitimate source and perfect presentation of real knowledge whereas others find religion as another authentic source. This paradoxical view created a sense of conflict between science and religion. Forward with that, this study examines this hyped-conflict within the framework of the Quran, the fundamental scripture of Islamic faith. It mainly highlights the question of the relation between human-obtained scientific truth and Quranic scientific revealed truth, and to a large extent the study stands as a commentary of scientism “the philosophy that takes for granted the idea of science being the nonpareil font for real lore”, which is in fact the crux of the matter. The research is carried out with the aim of mapping people’s perception towards conductivity of the Quran as an authentic, accurate and reliable source to investigate complex questions of modern world and maintaining its coexistence with science in a scientific age. To ensure a comprehensive understanding, the research provides a scientific-linguistic analysis of some selected Quranic verses dealing with embryology in addition to a data gathered out of a questionnaire for Muslim doctors. The findings of the study reveal that the view of discord is highly rejected from an Islamic perspective and prove that the Quran constructs a view of the scientific mind. In addition, it shows the great potential of harmony between both, Quran and science, regardless to their different domains